2023
DOI: 10.57187/smw.2023.40053
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative complications and oncological outcomes of post-chemotherapy retroperitoneal lymph node dissection in patients with germ cell cancer at two high-volume university centres in Switzerland – a retrospective chart review

Abstract: BACKGROUND: Post-chemotherapy retroperitoneal lymph node dissection (PC-RPLND) is an integral part of the management of patients with metastatic non-seminoma and residual masses >1 cm after chemotherapy. AIMS: To assess perioperative complications and oncological outcomes at two major referral centres in Switzerland. METHODS: This was a retrospective chart review of 136 patients with non-seminoma who underwent PC-RPLND between 2010 and 2020 at the university hospitals of Bern and Zürich. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Some studies on bilateral and unilateral post-chemotherapy robotic-assisted retroperitoneal lymph node dissection (PC-rRPLND) reported 0% recurrence rates [ 116 – 120 ]. However, a recent study [ 72 ] showed a 20.6% recurrence rate in patients who underwent PC-rRPLND, while other studies [ 121 – 123 ] reported relapse rates of 4.65%, 6.7%, and 8%, respectively. The limited research and varying results in this area indicate a need for further studies to explore possible mediators of these outcomes.…”
Section: Therapeutic Role Of Lnd In Tcmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies on bilateral and unilateral post-chemotherapy robotic-assisted retroperitoneal lymph node dissection (PC-rRPLND) reported 0% recurrence rates [ 116 – 120 ]. However, a recent study [ 72 ] showed a 20.6% recurrence rate in patients who underwent PC-rRPLND, while other studies [ 121 – 123 ] reported relapse rates of 4.65%, 6.7%, and 8%, respectively. The limited research and varying results in this area indicate a need for further studies to explore possible mediators of these outcomes.…”
Section: Therapeutic Role Of Lnd In Tcmentioning
confidence: 99%
“…Notably, there are no statistically significant differences in complication rates between lRPLND and rRPLND [ 67 – 69 ]. Several studies have reported reduced complication rates with the unilateral template compared to the bilateral template [ 38 , 59 , 70 72 ]. Complications are more common in patients over 40 years old and in cases involving tumors larger than 20 mm [ 72 ].…”
Section: Anatomical and Surgical Aspect Of Lymphadenectomymentioning
confidence: 99%
See 1 more Smart Citation